Reaping the Rewards Later: How Education Improves Old-Age Cognition in South Africa - Plamen Nikolov; Steve Yeh (Institute of Labor Economics (IZA), 2022)
Cognitive performance in late adulthood is critical for better welfare and understanding the causes of human capital depreciation in old age is increasingly crucial in aging societies. Using data from South Africa, we study how early life education affects cognition, a component of human capital critical to decision-making, in late adulthood. We show that an extra year of schooling improves memory and general cognition performance. We detect heterogeneous treatment effects by gender: the effects are stronger among women. We explore mechanisms and show that a more supportive social environment, improved health habits, and reduced stress levels are likely mediators for the beneficial effects of increased educational attainment on old-age cognition.
Keywords: J14; J24; I21; F63; N37; 330; human capital; educational attainment; cognitive performance; developing countries; aging; sub-Saharan Africa